Self-Efficacy, Teacher’s Attitude, and English Language Learning Achievements - Haibar, Rizky Allivia Larasati; Yuzarion, Yuzarion (Bulletin of Counseling and Psychotherapy, 2024)
Student’s learning achievement is affected by internal and external factors. This study aimed to discover the relationship between self-efficacy and teachers' attitudes with SMP N (State Junior High School) 1 Bantul student learning achievement in English language subjects. The self-efficacy variable is considered the internal factor, while the teacher’s attitude is one of the external factors. This study is quantitative research using the non-experimental research design and correlational approach. The research population involved 320 students of Grade VIII of SMP N 1 Bantul, selected using the cluster random sampling technique. The research data were collected using the self-efficacy scale adapted from Gafoor & Ashraf (2006), the teacher’s attitude scale compiled by Yuzarion (2014), and students’ final semester examination grades from the Even Semester Year 2022/2023. The data analysis technique applied to analyze these data was multiple linear regression using the assistance of the SPSS application. In the minor hypothesis testing, an R-value of .539 was obtained for the self-efficacy variable, and .690 for the teacher attitude variable with a probability value of .000. Based on the results of multiple regression analysis for the major hypothesis, an R-value of .701 was obtained with a probability value of .000. These results mean that there is a strong relationship between self-efficacy and teacher attitudes towards student’s learning achievement. The effective contribution separately for the self-efficacy variable is 8.8% and 40.3% for the teacher attitude variable. The total effective contribution is 49.1%, with the remaining 50.9% influenced by other variables not discussed in this research.